Analisis Implementasi Kebijakan Pengendalian Pemotongan Ternak Sapi dan Kerbau Betina Produktif di Provinsi Bengkulu - Indah Permatasari; Slamet Widodo; Sugeng Susetyo (The Manager Review, 2021)
The objectives of this study were: (1) To analyze the implementation of control of productive slaughtering of cattle and female buffalo in Bengkulu Province based on George Edward III's policy implementation model, namely communication, resources, disposition of bureaucratic structures. (2) To analyze the implementation constraints of slaughtering productive female cattle and buffalo in Bengkulu Province. This research is a qualitative research with a descriptive design. Determination of informants in this study using the purpusive method, namely the maker and executor of policies to control the slaughter of productive female cattle and buffalo in Bengkulu Province as many as 9 people. The data collection used interviews and observations, while the descriptive qualitative data analysis was based on the Miles and Huberman stages. The results showed that the implementation of the control of productive female cattle and buffalo slaughter in Bengkulu Province from the aspects of (1) communication, that the delivery of information through socialization and distribution of brochures during the coaching activities of livestock groups. The submission of this information is only done once per year due to budget constraints. In terms of clarity, it is very clear from the district level to all parties involved in this policy, starting from the farmer level, business actors, and the regions involved. (2) Resources enough official personnel are available, but the veterinary paramedics are still lacking. Budget support for 2020 has experienced budget recofusing, so that for 2020 there will be no more activities. The local government is very supportive of the implementation of the control of productive female cattle slaughter. Then the supporting facilities are generally available, but for the facilities in the RPH starting from the building and other equipment it is necessary to make improvements and add to the facilities. (3) Disposition, that the local government and the community can accept it quite well. Related to incentives for policy implementers only for officers reporting daily deductions. (4) The bureaucratic structure, that the organizational structure is not yet supportive because the SOP prohibiting the slaughter of productive females is only owned by Mukomuko District, while all districts / cities do not yet exist. When viewed from the perspective of work effectiveness, managing this program is optimal, because it involves almost all sectors implementing this policy